Les mâts d’ornement des pylônes aux époques ptolémaïque et romaine: entre réalité et idéal - Martzolff, Laetitia (Zeitschrift für ägyptische Sprache und Altertumskunde, 2012)
Numerous representations of pylons, formed from towers and front masts, remain from the New Kingdom. The images square with several texts describing pylons and tally with archaeological finds which prove that masts were erected in front of the towers. In the Ptolemaic and Roman periods, the form of the pylon was used several times in architecture. Constructions of this kind, though from their outer aspect they are reminiscent of New Kingdom monuments, yet present architectural novelty: their towers are hollow. As for the masts however, to judge from the evidence provided by archaeological finds, they seem to have ceased to be erected, though they are still mentioned in texts. This article investigates each pylon and takes into consideration other kinds of documentation in two and three dimensions (models, coins, pictures) in order to analyse the situation of the masts and to understand how the monument was understood by architects and artists. The conclusions are that they were idealizing the pylons with their masts and the fixation system, for, in fact, masts generally stopped being placed in front of the pylon-towers. Various factors lie behind this change. An explanation based on the dimensions of the monuments is here put forward but a possible problem of wood supply can be another factor.